Notes on phalangiidae (Arachnida: Opiliones) of southern Africa with description of new species and comments on within-species variation - Taylor, Christopher (Magnolia Press, 2017)
Notes are provided on a collection of Afrotropical harvestmen (Opiliones: Palpatores: Phalangiidae) from the California Academy of Sciences. A new species of Rhampsinitus, R. conjunctidens n. sp., is described from Limpopo province of South Africa. Rhampsinitus flavobrunneus Starega 2009 and R. silvaticus Lawrence 1931 are recognised as junior synonyms of R. nubicolus Lawrence 1963 and R. vittatus Lawrence 1931, respectively. Both R. conjunctidens and R. nubicolus are recognised as exhibiting strong male dimorphism with major males exhibiting larger body size and greatly enlarged chelicerae relative to minor males; minor males cannot be readily identified to species without examination of genitalia. A discussion is also provided on generic boundaries within Afrotropical Phalangiidae, and a generic key to males of the region is presented.